Time-resolved dynamics in single InGaN quantum dots - Taylor, R; Robinson, J; Rice, J; Lee, K; Jarjour, A; Na, J; Yasin, S; Oliver, R; Kappers, M; Humphreys, C; Andrew, G; Briggs, D; et al. (2005)
We present measurements of microphotoluminescence decay dynamics for single InGaN quantum dots. The recombination is shown to be characterized by a single exponential decay, in contrast to the non-exponential recombination dynamics seen in the two-dimensional wetting layer. The lifetimes of single dots in the temperature range 4 K to 60 K decrease with increasing temperature. Microphotoluminescence measurements of exciton complexes in single MOVPE-grown InGaN quantum dots are also reported. We find the exciton-biexciton and exciton-charged exciton splitting energies to be 25 meV and 10 meV to the higher-energy side of the exciton ground state, respectively. Assignments of the ground state exciton, biexciton and charged exciton are supported by theoretical calculations. These measurements have been extended to investigate the time-resolved dynamics of biexciton transitions in the quantum dots. The measurements yield a radiative recombination lifetime of 1.0 ns for the exciton and 1.4 ns for the biexciton. The data can be fitted to a coupled differential equation rate equation model, confirming that the exciton state is refilled as biexcitons undergo radiative decay.